Dataveillance in the workplace: Managing the impact of innovation - Cliona McParland; Regina Connolly (Business Systems Research (BSR), 2020)
Background: Monitoring and surveillance are a fundamental part of the workplace environment, with employee performance and productivity as the main objects of scrutiny. However, many questions surround the ethical nature of managements' ability to employ advanced digital technologies to monitor employee behaviour and performance while in the workplace. If unaddressed, these concerns have the potential to significantly impact the relationship between the employee and the employer, impacting trust in management resulting in negative attitudes and counterproductive behaviours. Objectives: The goal of this paper is to present a comprehensive review of workplace surveillance whilst outlining some of the emerging issues relating to the use of employee monitoring technologies in the workplace. Methods/Approach: A detailed review of the literature was conducted in order to identify the major issues relating to workplace surveillance. In addition, a number of practitioner-based studies were examined to extract and identify emerging trends and concerns at an industry level. Results: Workplace surveillance is on the rise; however, empirical studies are in short supply. Conclusions: The issue of workplace surveillance is an under-researched area, which requires much attention. There is a distinct need for clear measures and structures that govern the effective and fair use of communication technologies in the workplace.
Keywords: O3; 330; employee privacy concerns; monitoring; trust; workplace surveillance; employee empowerment; counterproductive workplace behaviour; psychological contract